Pengaruh Model Problem Based Learning Berbantu Museum Virtual Terhadap Kemampuan Berpikir Kritis Siswa di SMKN 1 Kab. Tangerang - Dita Amalia; Rikza Fauzan; Ana Nurhasanah (Journal on Education, 2024)
The learning process is one of the efforts to improve students’ critical thinking skills in the field of education especially in the subject of history. Howover looking at the facts in the field the learning process in history subjects has not referrd to efforts to develop students’ critical thinking skills especially at SMKN 1 Kab. Tangerang. The purpose of thes study aims to determine whenether there is an influence of the use of the Problem Based Learning model assisted by virtual on students’ critical thinking skills in class XI at SMKN 1 Kab. Tangerang. To find answer to the stated research objectives, this study uses the Quasi Experimental activities. This study uses XI TKJ 3 as the experimental class and XI TKJ 2 as the control class. After analiyzing the research result, it was found that there was an influance of the use of the Prooblem Based Learning model helped by virtual museum on critical thinking skills in class XI Students’ at SMKN 1 Kab. Tangerang. This based on calcution of the t-test using microsoft excel. The t-count values of 6,568 is not equal to greather than the t-tabel values of 2,0402 throught a significance level of 5%, so the conclusion obtained is that there is ann influance of the Problem Based Learning model assisted by a virtual museum on critical thinking skills of class XI sudents at SMKN 1 Kab. Tangerang. Keywords: Problem Based Learning Model, Virtual Museum, & Critical Thinking